2017
DOI: 10.1017/s002237781700071x
|View full text |Cite
|
Sign up to set email alerts
|

Particle acceleration in relativistic magnetic flux-merging events

Abstract: (Received xx; revised xx; accepted xx)Using analytical and numerical methods (fluid and particle-in-cell simulations) we study a number of model problems involving merger of magnetic flux tubes in relativistic magnetically-dominated plasma. Mergers of current-carrying flux tubes (exemplified by the two dimensional "ABC" structures) and zero total current magnetic flux tubes are considered. In all cases regimes of spontaneous and driven evolution are investigated.We identify two stages of particle acceleration … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
80
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(86 citation statements)
references
References 69 publications
(144 reference statements)
5
80
1
Order By: Relevance
“…The non-thermal particle fraction increases with the magnetization. Similar studies have also been carried out independently by Lyutikov et al (2016) recently.…”
Section: Introductionsupporting
confidence: 68%
See 2 more Smart Citations
“…The non-thermal particle fraction increases with the magnetization. Similar studies have also been carried out independently by Lyutikov et al (2016) recently.…”
Section: Introductionsupporting
confidence: 68%
“…Another possibility involves the polar jet, which has relatively high magnetization and is kink unstablesuggesting that it possesses free magnetic energy. Recently, Lyutikov et al (2016) also proposed that the intermediate latitude post shock flow can produce regions with high magnetization and current carrying filaments, resembling the flux tubes in force-free configurations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, relativistic reconnection could be important in pair plasmas (see Kagan et al 2015, and references therein), and in particular it should be an ingredient in the modeling of Pulsar Wind Nebulae in order to explain dissipation of magnetic energy in the so-called striped wind region (Coroniti 1990;Kirk & Skjaeraasen 2003;Pétri & Lyubarsky 2007;Amano & Kirk 2013;Takamoto, Pétri & Baty 2015), and the sudden gamma-ray flares observed in the Crab nebula, probably originated in the vicinities of the wind termination shock (Tavani 2013;Baty, Petri & Zenitani 2013;Cerutti et al 2014;Lyutikov et al 2016). Promising results are starting to come from two-fluid relativistic MHD simulations (Barkov et al 2014;Barkov & Komissarov 2016), as a viable alternative to fully kinetic particle-in-cell (PIC) methods, which are more computationally demanding.…”
Section: Introductionmentioning
confidence: 99%
“…These simulations, which focus on the pair-plasma case which is easier to simulate and is directly applicable to the Crab Nebula, have shown that relativistic reconnection can produce hard non-thermal tails of highly accelerated particles that are typically interpreted as power laws (Zenitani & Hoshino 2001, 2005, 2007Zenitani & Hesse 2008;Jaroschek et al 2004Jaroschek et al , 2008Bessho & Bhattacharjee 2005, 2007, 2012Daughton & Karimabadi 2007;Lyubarsky & Liverts 2008;Liu et al 2011;Cerutti et al 2012bCerutti et al , 2013Cerutti et al , 2014Werner et al 2016;Sironi & Spitkovsky 2014;Sironi et al 2016;Guo et al 2014Guo et al , 2015Liu et al 2015;Yuan et al 2016;Lyutikov et al 2016;Kagan et al 2016). In general, the physics of reconnection is similar in two and three dimensions (Sironi & Spitkovsky 2014) unless the initial reconnection structure is inherently three-dimensional, justifying the use of two-dimensional simulations which reduce computational cost and allow larger-scale simulations to be carried out.…”
Section: Introductionmentioning
confidence: 99%